G-Quadruplexes Regulate miRNA Biogenesis in Live Zebrafish Embryos - Steeman, Tomás José (2023)
RNA guanine quadruplexes (G4s) regulate RNA functions, metabolism, and processing. G4s formed within precursors of microRNAs (pre-miRNAs) may impair pre-miRNAs maturation by Dicer, thus repressing mature miRNA biogenesis. As miRNAs are essential for proper embryonic development, we studied the role of G4s on miRNA biogenesis in vivo during zebrafish embryogenesis. We performed a computational analysis on zebrafish pre-miRNAs to find putative G4 forming sequences (PQSs). The precursor of the miRNA 150 (pre-miR-150) was found to contain an evolutionarily conserved PQS formed by three G-tetrads and able to fold in vitro as G4. MiR-150 controls the expression of myb, which shows a well-defined knock-down phenotype in zebrafish developing embryos. We microinjected zebrafish embryos with in vitro transcribed pre-miR-150 synthesized using either GTP (G-pre-miR-150) or 7-Deaza-GTP, a GTP analogue unable to form G4s (7DG-pre-miR-150). Compared to embryos injected with G-pre-miR-150, embryos injected with 7DG-pre-miR-150 showed higher levels of miRNA 150 (miR-150) and lower levels of myb mRNA and stronger phenotypes associated with myb knock-down. The incubation of pre-miR-150 prior to the injection with the G4 stabilizing ligand pyridostatin (PDS) reverted gene expression variations and rescued the phenotypes related to myb knock-down. Overall, results suggest that the G4 formed in pre-miR-150 functions in vivo as a conserved regulatory structure competing with the stem-loop structure necessary for miRNA biogenesis.